1992
DOI: 10.1080/09553009214551621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fluoride on Photodynamic-induced Fluorescence Changes of Aluminium Phthalocyanine in Chinese Hamster Cells

Abstract: Fluence-dependent changes in the fluorescence of aluminium phthalocyanine (AlPc) were measured in Chinese hamster ovary (CHO) cells using digital fluorescence microscopy of single cells and spectrofluorimetry of cell suspensions. During illumination the fluorescence initially increased and later progressively decreased. In the presence of fluoride, which protects against phototoxicity of AlPc by forming a fluoroaluminium complex, there was no initial increase in fluorescence: it decreased about 10 times faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Singlet oxygen ( 1 O 2 ) reacts with a large variety of biological molecules such as DNA, lipids, and proteins and has a damaging effect on them. 23,24 It was revealed that extremely small amounts of ( 1 O 2 ) could cause changes in the redox status of a cell. In some cases, singlet oxygen may not be the primary mediator of photodynamic action, although its production is enhanced.…”
Section: Laser Radiation In Human Erythrocytementioning
confidence: 99%
“…Singlet oxygen ( 1 O 2 ) reacts with a large variety of biological molecules such as DNA, lipids, and proteins and has a damaging effect on them. 23,24 It was revealed that extremely small amounts of ( 1 O 2 ) could cause changes in the redox status of a cell. In some cases, singlet oxygen may not be the primary mediator of photodynamic action, although its production is enhanced.…”
Section: Laser Radiation In Human Erythrocytementioning
confidence: 99%